Dividendová strategie – součást behaviorální ekonomie - Fojtů, Kateřina; Škapa, Stanislav (Vysoké učení technické v Brně, Fakulta podnikatelská, 2013)
Purpose of the article: Purpose of this paper is criticaly analyse the role of dividend by using knowledge from the field of behavioral economics. Concepts such as moral hazard and asymmetric information are associated with behavioral finance and decision-making processes of companies. Behavioral economics sees the individual as irrational man who does not try to maximize his/her benefit, but mainly to minimize the risk in decision making. Against the background of the analyzed issue is made specific comparisons of dividend investment strategies with neutral/market strategies. Methods: Primary and secondary research was used in this article. Secondary research was based on a search of scientific articles and literature on the theory of dividend, shares and behavioral economics. Data from two previously conducted studies were used. Primary research was conducted on two stock indexes (dividend strategy vs. neutral/market strategy) using selected statistical methods, and then the connection was sought between dividend policy and the return that these strategies bring. Scientific aim: The aim of this paper was to make a critical analysis of investment dividend strategy compared with a neutral/market strategies using statistical methods. Findings: It can be concluded that long-term investing in dividend stocks gives the investor a slightly higher valuation, at about the same risk than investing in stocks covering the whole market. Conclusions: Based on the results of studies conducted by Credist Suisse, Professor Siegel and based on our research can be identified dividend strategy. This strategy provides one of the best conditions return and risk, both in the development of the medium-term and long-term trend. This strategy follows the newly formed STOXX indexes, DJ, MSCI, S & P or WisdomTree.
Dividend Strategy – Part of Behavioral Economics
Keywords: behavioral economics; stocks; dividends; dividend theories; stock indexes